Pendampingan Pengoptimalan Pengelolaan Konten Website Dan Literasi Digital Di Yayasan Rumah Langit - Windhiadi Yoga Sembada; Andhika Octa Indarso; Irpan Ripa’I Sutowo (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Rumah Langit Foundation is an institution engaged in the social sector, namely fostering the children of scavengers in the Gedong village area, Kramat Jati, East Jakarta. Rumah Langit has aspirations to inspire children. The Rumah Langit Foundation has a website that is designed to provide information access space for the public to get to know the vision, mission and activities carried out by the foundation. On the other hand, the children assisted by this foundation have smart phones from their scavengers profession. It is feared that this new habit will expose the fostered children to sensitive or negative content if they do not receive proper guidance. The presence of this activity is expected to be able to optimize the existing website and be able to inform the wider community so that it invites more participation and provides briefing to avoid the negative impact of the internet.